FORMATION OF SELF-EDUCATIONAL COMPETENCE FUTURE EDUCATORS PRESCHOOL EDUCATION INSTITUTIONS - Potapchuk, Tetiana; Kravets, Nadija (Educological discourse, 2021)
In the article self-education as a component of professional training acts as a way to implement it. In this context, the self-education of future educators, we mean the process that ensures the continuity of raising the educational level and expanding the information field of professionals, improving the quality and raising the level of their competence and professionalism, related to personal development and participation in general and pedagogical culture. Serves to form a worldview, because the student is the subject of management of their own educational activities during professional training. Based on the analysis of different approaches to the definition of "self-educational competence" in the context of this study, we consider this term as an integrative phenomenon characterized by stable internal motivation, the formation of professionally significant personal qualities, skills and abilities to organize cognitive personality. search activities aimed at a continuous process of professional development; and is an integral part of the professional competence of the specialist and an indicator of the success of his professional activity. Given the above, it is possible to state the close connection between the concept of "self-education" and the concept of "vocational training"; self-education should be understood as a way to implement this training, which, accordingly, aims to form a skilled worker capable of developing strategies for professional development as a result of self- education. This is one of the most important prerequisites for further professional realization of him as a specialist In this regard, higher education faces the task of developing more effective learning technologies and creating conditions that would be focused on stimulating students’ self- education. The purpose of the article is to theoretically substantiate the key concepts "educator", "future educator", "self-education", "competence", "formation of self- educational competence". Methods: analysis, systematization and generalization of psychological and pedagogical literature in order to clarify the state of development of the research problem and clarify the conceptual apparatus.